Respect the Resection. (5th July 2022) - Odom, Nicole; Thadani, Vijay M.
Abstract : An American Academy of Neurology practice parameter from 2003 recommends referral of patients with refractory epilepsy to an epilepsy surgery center. 1 Yet, epilepsy surgery remains underutilized relative to the number of patients who might benefit from it. These facts are well known to specialists in the field, but nonepileptologists seem less aware or less inclined to follow the recommendations. Despite the published parameters, there did not seem to be an improvement in the referral pattern over time, particularly for racial minorities and the underinsured. 2 Reasons for this are many. Potential contributing factors include a lack of knowledge about which patients may benefit from epilepsy surgery and what is the chance of seizure freedom for a particular patient. In addition, over the past decade, newer technologies such as stereoelectroencephalography (SEEG), laser interstitial thermal ablation (LiTT), responsive neurostimulation (RNS), and deep brain stimulation (DBS) are becoming more widely used 3 and further add to the complexity. Despite 2 centuries of experience with epilepsy surgery, knowing which patients will benefit the most from what therapy, especially for more complicated patients undergoing intracranial evaluation for the treatment of epilepsy, remains elusive.